DINAR EMAS SEBAGAI MEDIUM BERWAKAF TUNAI MENELITI KEPADA ASPEK PELAKSANAAN DAN SEJARAH ISLAM - Hamid, Che Khadijah; Yahaya, Salimah; Hassan, Surita Hartini Mat; Abdullah, Sakinatul Raadiyah; Fazial, Farahdina; Mohd Nor, Nor Adila (Jurnal 'Ulwan, 2024)
Gold dinars are goods derived from precious and valuable metals. The special features of gold metal make its use as the most popular currency compared to any other metal in the history of currency. Research on the mechanism currently used in the practice of cash waqf using fiat money as a waqf instrument. Therefore, the use of fiat money is feared to interfere with the perpetuity of ain' in the practice of waqf. In relation to that, this study highlights a basis regarding the use of gold dinar as a waqf medium from the perspective of Islamic history. First, the objective of this study is to analyze the implementation mechanism of cash waqf in Islamic history. Second, identify the basis of the gold dinar as a waqf medium in Islamic history. This study was formed through an exploratory study. Data collection is obtained from document review. Data were analyzed using content analysis methods. The research results found that the concept of cash waqf in Islamic history is based on capital loans, the loan mechanism is in the form of using gold money. Clear evidence of the gold dinar as a waqf mechanism has been identified in the Uthmaniyyat Period as a source of loan financing for waqf recipients at that time.